Multicenter Studies in Clinical Research: Benefits, Challenges, and Recommendations forEffective Management - Piccinino, Agustina L.; Ricasoli, Martina C.; Vaena, Mariana; Braslavsky, Ana; Grande Ratti, María F. (Revista del Hospital Italiano de Buenos Aires, 2026)
In clinical research, multicenter studies represent a key tool for collecting data from multiple centers, thus increasing the external validity and generalizability of results. The fact that they are conducted simultaneously in several institutions, localities, provinces, or even countries allows for a larger and more diverse sample, which favors representativeness and makes the information applicable to different populations and settings.This narrative review highlights their advantages and disadvantages and explores in depth the main challenges they entail (ethical, methodological, logistical, and operational). It also analyzes real and relevant examples that illustrate their impact on the generation of robust clinical evidence. Finally, conclusions and practical recommendations for the effective management of these projects are presented, emphasizing the importance of leadership, coordination between centers, the commitment of the research team, and rigorous adherence to ethical and methodological standards.
Keywords: Epidemiologic Studies; Biomedical Research; Multicenter Studies as Topic; Data Management; Reproducibility of Results; argentina